Analysis of the spillover characteristics of cooling effect in an urban park: A case study in Zhengzhou city - Gao, Yu; Pan, Huifeng; Tian, Li (Frontiers in Earth Science, 2023)
Urban parks effectively cool surrounding environment through heat exchange. This phenomenon is called spillover of park cooling effect (PCS) and it plays an important role in regulating microclimate of cities. Although PCS was extensively documented in previous studies, effects of park landscape features on PCS remain largely unclear. In this study, we chose Zhengzhou City (in central region of China) as an example, which has experienced rapid urban land expansion and urban population. We used Landsat 8 imagery and high score data in summer of 2019 to retrieve the characteristics of land surface temperature (LST), then we extracted 36 city parks, and identified spillover distance of park cooling effect (PCSD), spillover strength of park cooling effect (PCSS), spillover rate of park cooling effect (PCSR) and 11 park landscape indexes. We calculated the area threshold when a park achieves the highest cooling efficiency and the PCS characteristics of each park also were quantified. The results showed that the average LST of urban parks was 2.3 ℃ lower than that of the entire study area; PCSS was 4.61 ℃ at a maximum; PCSD was between 31-370 m, and the average value was 179 m; the average PCSR was 0.957 ℃/100 m. For the relation PCS with the 11 park landscape indexes, we found park area (AREA), park green space area (AREAg) and park perimeter (PERIM) contributed the most to PCS. Shape of impervious surface (LSIi) and percentage of water body (Pw) also high contributed to PCS. The ratio of perimeter to area (PARA), edge density (ED), edge density of the green space (EDg), and patch density (PD) were significantly and negatively correlated with PCS. For the relationship between park area and PCS, the result was when the park with an area of 6-8 ha and an internal green area of not less than 5-6 ha has the highest PCS effect. This study can expand our scientific understanding on influences of park landscape characteristics on PCS, and provide a scientific basis for formulating reasonable and effective urban parks and spatial layout planning to cope with urban heat island effect.